People watching: Abstractions and orthodoxies of monitoring - John Tucker (Technology in Society, 2023)
Our society has an insatiable appetite for data. Much of the data is collected to monitor the activities of people, e.g., for discovering the purchasing behaviour of customers, observing the users of apps, managing the performance of personnel, and conforming to regulations and laws, etc. Although monitoring practices are ubiquitous, monitoring as a general concept has received little analytical attention. We explore: (i) the nature of monitoring facilitated by software; (ii) the structure of monitoring processes; and (iii) the classification of monitoring systems. We propose an abstract definition of monitoring as a theoretical tool to analyse, document, and compare disparate monitoring applications. For us, monitoring is simply the systematic collection of data about the behaviour of people and objects. We then extend this concept with mechanisms for detecting events that require interventions and changes in behaviour, and describe five types of monitoring.We argue for the development of a general theory of monitoring.